Integrated laboratory classes to learn physiology in a psychology degree: impact on student learning and experience - Sánchez, Judit; Navarro-Galve, Beatriz; Lesmes, Marta; Rubio, Margarita; Gal, Beatriz (Frontiers in Psychology, 2023)
Physiology is a fundamental discipline to be studied in most Health Science studies including Psychology. Physiology content is perceived by students as rather difficult, who may lack vision on how to relate it with their professional training. Therefore, identifying novel active and more engaging pedagogical strategies for teaching physiology to psychology students may help to fill this gap. In this pilot study, we used the PBL methodology developed around a clinical case to evaluate psychology students’ experience and learning in two laboratory classes modalities. The aim of this study was to compare the undergraduates’ preference for laboratory classes taught either independently (cohort 1, n = 87 students) or integrated into the PBL-oriented clinical case (cohort 2, n = 92 students) for which laboratory classes were transformed into Integrated Laboratory Classes (ILCs). The students’ academic performance was also evaluated to look for quantitative differences between cohorts. We found similar overall academic scores for the Physiology course between cohorts. Interestingly, when we compared the academic scores obtained in the theoretical content from each cohort, we found a significant improvement (p < 0.05) in cohort 2 where the students achieved better results as compared to cohort 1. A subset of students was asked to fill a questionnaire assessment on their experience and found that 78.9% of them preferred integrated laboratory classes over laboratory classes alone. They consistently reported a better understanding of the theoretical content and the value they gave to ILCs for learning. In conclusion, our pilot study suggests that integrating laboratory classes into PBL-oriented clinical contexts help to retain core physiology contents and it can be considered as an engaging learning activity worth implementing in Psychology teaching.